Representación discursiva del empoderamiento femenino en la subtitulación de la adaptación cinematográfica Little Women (2019) - Durán Aramburú, Grecia Milagros (2023)
Historically, women have played an inferior role to men and have been victims of mistreatment, situations of discrimination and experiences of inequality only because of their status as women. This has been represented in many audiovisual products, where inequality and the perpetuation of stereotypes related to the role of women have been shown very naturally. Nevertheless, with the ideological evolution of society, we see much more frequently audiovisual productions that no longer follow the same pattern that denigrates women, but, on the contrary, shows her as a brave, strong, and capable character. These products have generated a change in movies, series, and advertisements and in their consumers in the last years. Due to this, the present investigation takes as its object of study the film Little Women (2019), characterized by the message of female empowerment it transmits. This seeks to analyze how this empowerment has been represented and translated in its Spanish subtitling. The study will employ the multiple case study methodology and three research techniques will be used to fully address all the objectives of the research, which are: the content analysis, the contrastive textual analysis, and the interview.